2020
DOI: 10.4067/s0034-98872020000100069
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anthropometric nutritional status and functional capacity in older adults living in the community

Abstract: Background: The functional fitness of older people may be associated with their nutritional status. Aim: To assess the association between of anthropometric measures with functional fitness in older people. Material and Methods: Cross-sectional study conducted in 75 participants aged 65 to 89 years. Body mass index (BMI), waist-to-height ratio (WHtR), fat mass (FM) and skeletal muscle mass index (SMI) were calculated from anthropometric measures. The functional fitness was determined using the Senior Fitness T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several anthropometric variables have been previously suggested to be associated with aerobic capacity among older adults [ 24 , 25 ] and have been proposed to identify adults at risk of physical limitations and multimorbidity based on age [ 26 , 27 ]. A negative association between HRQoL and arterial pressure has been reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several anthropometric variables have been previously suggested to be associated with aerobic capacity among older adults [ 24 , 25 ] and have been proposed to identify adults at risk of physical limitations and multimorbidity based on age [ 26 , 27 ]. A negative association between HRQoL and arterial pressure has been reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hormonal changes at menopause put women at risk for increased body weight and visceral fat deposition, while also decreasing fat-free mass and reducing muscle mass. The reduction in muscle mass leads to a lower basal metabolic rate and a progressive reduction in total energy expenditure, also contributing to the increase in fat tissue [ 4 , 12 ]. This divergence in response to aging between sexes, yet greater longevity experienced by women highlight the challenge communities face when dealing with health and wellcare of aging women.…”
Section: Discussionmentioning
confidence: 99%
“…Guede-Rojas et al. [ 12 ], revealed that older men out performed women on 2 functional tests, the 2-min step test and the sit-and-reach test. Tangen et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the multivariable logistic regression also suggest that gender, age, and BMI are major determinants of SMI. Other studies have also shown that these are important factors that influence SMI [ 36 39 ]. Owing to our small sample size, it is difficult to generalize our research results regarding the determinants of SMI.…”
Section: Discussionmentioning
confidence: 99%